Degradation of Reactive Blue 181 Dye by Heterogeneous Fenton Technique Using Modified Fly Ash - Sy Duc, Dao (Asian Journal of Chemistry, 2013)
In this paper, the heterogeneous Fenton technique using modified fly ash used for the degradation of Reactive Blue 181. The catalysts were prepared supporting the metal by the incipient impregnation method using iron(III) nitrate. Several properties of raw and modified fly ashes were characterized by SEM, EDX and XRD techniques. Effects of some key operating parameters such as catalyst dose, pH and the concentration of hydrogen peroxide on the treatment efficiency were studied and discussed. Kinetic rate constants of treatment process were also determined. The experimental results show that the heterogeneous Fenton technique using modified fly ash/H2O2 is a suitable method for removing Reactive Blue 181 from aqueous solution. At the optimum conditions include pH 3; catalyst dose of 0.4 g/L, hydrogen peroxide concentration of 3.92 mM, treatment time of 90 min, approximately 90 % of Reactive Blue 181 was removed from aqueous solution. The kinetic data fitted well for pseudo first-order reaction.